Exploring participatory scenario planning for sustainable urban tourism development - Miranda Cornelisse; Arjen van Klink (Research in Hospitality Management)
This viewpoint article explores the potential of multistakeholder participatory scenario planning (PSP) as a tool to foster a sustainable visitor economy in underprivileged neighbourhoods. Feijenoord, a district in Rotterdam, is such an area. While the visitor economy offers economic benefits, it can also pose negative effects like social fragmentation. Although PSP has shown promise in similar contexts, stakeholder selection, heterogeneity within groups, individual creativity, managing conflicts and sustaining long-term commitment are critical issues. With their students, universities can take a role facilitating PSP and stimulating learning. We believe in the connection between higher education and the professional field, particularly when it comes to envisioning future perspectives and translating those visions into action.